“Daremnie próbuje się wybielić Etiopa” – postrzeganie i polityka Bizancjum wobec koczowników stepów czarnomorskich (X-XII w.) - Paroń, Aleksander (Vox Patrum, 2020)
The problem of relations with the nomadic peoples of the Black Sea steppes is one of the most important issues in Byzantine history. The medieval Greek-speaking Romans inherited this undisputed trouble from their ancient ancestors and had to deal with it until the end of the Empire. It is usually assumed that the long experience of contacts with steppe-dwellers meant that the Byzantine political elite gained a deep and multi-faceted knowledge of them. This study is an attempt at rethinking the communis opinio according to which precise and updated data had to be used by the Constantinopolitan diplomacy in relations with the nomadic partners. What I aim to prove, based on the material of written sources from between the 10th and 12th centuries, is that such opinions appear to have been scholarly superstitions.